FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Borges, Vanessa de Fátima (2023)
Objective: This study aimed to investigate the effects of FK506 on experimental sepsis immunopathology. It investigated the effect of FK506 on leukocyte recruitment to the site of infection, systemic cytokine production, and organ injury in mice with sepsis. Methods: Using a murine cecal ligation and puncture (CLP) peritonitis model, the experiments were performed with wild-type (WT) mice and mice deficient in the gene Nfat1 (Nfat1−/−) in the C57BL/6 background. Animals were treated with 2.0 mg/kg of FK506, subcutaneously, 1 h before the sepsis model, twice a day (12 h/12 h). The number of bacteria colony forming units (CFU) was manually counted. The number of neutrophils in the lungs was estimated by the myeloperoxidase (MPO) assay. The expression of CXCR2 in neutrophils was determined using flow cytometry analysis. The expression of inflammatory cytokines in macrophage was determined using ELISA. The direct effect of FK506 on CXCR2 internalization was evaluated using HEK-293T cells after CXCL2 stimulation by the BRET method. Results: FK506 treatment potentiated the failure of neutrophil migration into the peritoneal cavity, resulting in bacteremia and an exacerbated systemic inflammatory response, which led to higher organ damage and mortality rates. Failed neutrophil migration was associated with elevated CXCL2 chemokine plasma levels and lower expression of the CXCR2 receptor on circulating neutrophils compared with non-treated CLP-induced septic mice. FK506 did not directly affect CXCL2-induced CXCR2 internalization by transfected HEK-293 cells or mice neutrophils, despite increasing CXCL2 release by LPS-treated macrophages. Finally, the CLP-induced response of Nfat1−/− mice was similar to those observed in the Nfat1+/+ genotype, suggesting that the FK506 effect is not dependent on the NFAT1 pathway. Conclusion: Our data indicate that the increased susceptibility to infection of FK506-treated mice is associated with failed neutrophil migration due to the reduced membrane availability of CXCR2 receptors in response to exacerbated levels of circulating CXCL2.